2020
DOI: 10.3390/su12166608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reversal of Conservation Tillage on Soil Nutrient Availability and Crop Nutrient Uptake in Soybean in the Vertisols of Central India

Abstract: Effect of conservation tillage on crop performance and soil properties has been studied extensively under different agro-climatic situations. However, the impact of reversal from conservation tillage to conventional tillage on crop growth and soil nutrient release is rarely addressed. Thus, this study was conducted by converting half of the eight years old conservation tillage experiment to the conventional one with a similar level of residue return to compare the effect on soil nutrient availability and nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
4
13
0
1
Order By: Relevance
“…Under the reduced tillage system and direct drilling, nutrients are unevenly distributed due to their greater accumulation in the top soil layer [5,7,17,55,[60][61][62]. Under such tillage conditions, the accumulation of crop residues in the surface soil layer promotes a higher concentration of P, K, and Mg, compared with conventional tillage [7,16,31,63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the reduced tillage system and direct drilling, nutrients are unevenly distributed due to their greater accumulation in the top soil layer [5,7,17,55,[60][61][62]. Under such tillage conditions, the accumulation of crop residues in the surface soil layer promotes a higher concentration of P, K, and Mg, compared with conventional tillage [7,16,31,63].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the loss of SOM has a negative effect on soil structure, water capacity, and biological activity. It also increases susceptibility to water and wind erosion [1][2][3][4][5][6]. The degradation of the soil environment associated with conventional soil tillage results in a need to use new tillage technologies that will allow the biodiversity of biocenosis to be preserved, including soil conservation [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil pH is reported to affect the availability, solubility as well as mobility of micronutrients. Previous research has shown that at high pH concentration, soil organic carbon and micronutrients become less soluble resulting in low concentrations in soil solution [39]. The percentage of adsorption of micronutrients is low at low pH concentrations, hence, the highest concentration of micronutrients was in the soil under NT compared to CT and RT which recorded high pH levels.…”
Section: Effects Of Tillage and Depthmentioning
confidence: 93%
“…It is regarded as a component of sustainable land management and better land husbandry approaches (Sastre et al 2018). Numerous investigations have reported that reduction in soil cultivation in relation to conservation or no tillage can significantly alter the distribution of plant available nutrients within the surface layer of soil (Singh et al 2020).…”
Section: Introductionmentioning
confidence: 99%